Design and Implementation of an Android-Based Financial Management Application for the Information Technology Study Program - Fajar, Alfaris; Jimmie; Karnadi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid development of mobile technology has encouraged the use of Android-based applications in various domains, including financial management. Students of the Information Technology Study Program often face difficulties in recording and managing personal income and expenses systematically, highlighting the need for a practical and accessible solution. This study aims to design and implement an Android-based financial management application to support efficient and structured financial administration. The research employs a Design and Creation methodology with a qualitative approach, following the Waterfall system development model that includes analysis, system design, implementation, and testing. The application was developed using Android Studio with the Kotlin programming language, featuring modules for recording income, expenses, assets, and generating financial reports. Functional testing using Black Box Testing indicates that the system operates according to specifications, while usability assessment shows that users can manage finances more effectively and intuitively. The findings suggest that the developed application reduces manual errors, improves data accessibility, and provides a reliable tool for managing personal finances. The application can be further enhanced with advanced features such as data analytics or intelligent recommendations to support decision-making in academic environments.